A comparative study of additive manufacturing techniques: Residual stress and microstructural analysis of CLAD and WAAM printed Ti-6Al-4V components - Szost, Blanka A.; Terzi, Sofiane; Martina, Filomeno; Boisselier, Didier; Prytuliak, Anastasiia A.; Pirling, Thilo; Hofmann, Michael; Jarvis, David John (Elsevier, 2015)
Nowadays, there is a great manufacturing trend in producing higher quality net-shape components of challenging geometries. One of the major challenges faced by additive manufacturing (AM) is the residual stresses generated during AM part fabrication often leading to unacceptable distortions and degradation of mechanical properties. Therefore, gaining insight into residual strain/stress distribution is essential for ensuring acceptable quality and performance of high-tech AM parts. This research is aimed at comparing microstructure and residual stress built-up in Ti–6Al–4V AM components produced by Wire + Arc Additive Manufacturing (WAAM) and by laser cladding process (CLAD).
Keywords: Residual stress; 3D printing; Titanium alloy; Neutron diffraction; Residual stress 3D printing Titanium alloy Neutron diffraction Wire + Arc Additive Manufacturing Laser cladding; Wire + Arc Additive Manufacturing; Laser cladding